Transformaciones territoriales y procesos de metropolización en Colombia: una aproximación a partir de la migración interna. (2016)
Migration flows to the main metropolitan areas of Colombia were analyzed, identifying processes of urban transformation related to distance, location and conditions of metropolitan development. We used information from the 2005 population census and results from the household survey of the National Administrative Department of Statistics. The results indicate that migrations were concentrated in the central area of the country and were characterized by being short distance, especially in intermediate cities. Similarly, a comparison of migration relations with indicators of metropolitan development suggests a certain deconcentration of the larger cities in an apparent demographic pressure towards the surrounding municipalities. This process is consistent with evidence from some cities in Latin America that go through a similar state of urban deconcentration called counter-urbanization.